Ore geology, fluid inclusion and isotope geochemistry of the Xunyang Hg–Sb orefield, Qinling Orogen, Central China. (6th May 2014) - Zhang, Ying; Tang, Hao‐Shu; Chen, Yan‐Jing; Leng, Cheng‐Biao; Zhao, Cheng‐Hai; Chen, Y.J.; Santosh, M.; Chen, H.Y.; Somerville, Ian
<x xml:space="preserve">Abstract</x> The Xunyang Hg–Sb orefield, Shaanxi Province, containing two large (Gongguan and Qingtonggou) and tens of small to medium Hg–Sb deposits, is located in the southern Qinling Orogen. Ore bodies of the deposits are hosted in Devonian dolomite and controlled by a fault system. Ores are mainly present as massive veins, disseminations, breccias and fine veinlets, with cinnabar (Hg) and stibnite (Sb) being the dominant ore minerals. Gangue minerals include quartz, calcite and dolomite. Hydrothermal minerals (quartz and calcite) only contain aqueous fluid inclusions with low homogenization temperature (135–274 °C) and salinity (1.23–12.3 wt.% NaCl equiv.), supporting an epizonogenic hydrothermal origin. The carbon, oxygen and hydrogen isotope data indicate that the ore‐forming fluids were mainly sourced from epizonogenic to metamorphic devolatilization of the Sinian−Triassic strata that possibly underthrusted beneath the orefield, with inflow of the circulating meteoric water. Sulphur isotope ratios of stibnite and cinnabar range from 2‰ to 12‰, suggesting a contribution from sedimentary sulphate or sulphate‐bearing fluids potted in strata, which is coincident with the δ34S values (3.4–8.6‰) of diagenetic pyrite in the strata. The conclusion drawn from sulphur isotopes is fully supported by the Pb isotope signatures. In addition, the 87Sr/86Sr ratios gradationally increase from ore‐hosting dolostones, through ore‐barren calcite or low‐grade ores, to high‐grade ores, indicating that a portion of the fluids originated from a source with higher 87Sr/86Sr values than the host‐rocks, which is possibly composed of the Neoproterozoic−Lower Palaeozoic basement of the Xunyang Basin. Integrating the data from ore geology, fluid inclusion microthermometry and stable, radioactive isotope geochemistry, it can be concluded that the deposits in the Xunyang Hg–Sb orefield were formed by epizonogenic hydrothermal fluids mainly sourced from the strata via structural deformation during the North China−Yangtze continental collision. Copyright © 2014 John Wiley & Sons, Ltd.